Post-Traumatic Stress Disorder (PTSD) Effect of Coronavirus (COVID-19) Pandemic and Role of Emotional Intelligence - Aida Mehrad, (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
Uncommon events during different decades and centuries create several challenges in the human lifestyle. Truthfully, individuals with any circumstances that have been occurred throughout their life illustrate various reactions and behaviours. In some cases, they report some issues such as Post-Traumatic Stress Disorder (PTSD) that is related to mental health which affected by any type of natural disasters, sickness, close relative dead, war, etc. At present, one of the crucial pandemic disasters caused by worldwide disease and death rates amongst individuals is Coronavirus (Covid-19) that has been spread enormous worries and anxiety in every society and country. The majority of individuals experienced this disaster and some of them demonstrate dissimilar types of anxiety and PTSD. The current literature review attempts to clarify the relation between Coronavirus (COVID-19) and PTSD based on the most recent investigations and reports, then link them to the role of Emotional Intelligence in reducing diverse unusual stress and severe nervousness such as PTSD that is the consequence of Coronavirus (COVID-19).